PERAN BRAND AWARENESS MEMEDIASI PENGARUH IKLAN DAN CELEBRITY ENDORSER TERHADAP NIAT BELI AVOSKIN DI DENPASAR - Wulandari, Kadek Ananda; Sukaatmaja, I Putu Gde (Buletin Studi Ekonomi, 2022)
This study aims to explain the role of brand awareness in mediating the effect of advertising and celebrity endorsers on the purchase intention of Avoskin skincare in Denpasar. This research was conducted using 102 respondents with a non-probability sampling method, especially purposive sampling. The analytical tool used in this research is PLS (Partial Least Square). The results of this study indicate that advertising and celebrity endorsers have a positive and significant effect on purchase intention. Advertisements and celebrity endorsers have a positive and significant effect on brand awareness. Brand awareness has a positive and significant effect on purchase intention. Brand awareness is significantly able to mediate the effect of advertising and celebrity endorsers on purchase intention. Therefore, it is important for the management of Avoskin to pay attention to advertisements and celebrity endorsers because these two things will affect consumers' purchase intentions. Likewise, brand awareness can increase consumer purchase intentions.